2020
DOI: 10.1159/000513050
|View full text |Cite
|
Sign up to set email alerts
|

Apelin-13: A Promising Biomarker for Age-Related Macular Degeneration?

Abstract: Purpose: To investigate the value of serum apelin-13 levels in age-related macular degeneration patients. Methods: Patients with dry-type AMD, treatment-naive neovascular-type AMD and the healthy control group were included in this study. Patients diagnoses were confirmed with detailed fundus examination, optical cohorence tomography and fundus flourescein angiography findings. Central foveal thickness and subfoveal choroidal thickness were evaluated. Both serum apelin-13 and vascular endothelial growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
(46 reference statements)
1
0
0
Order By: Relevance
“…VEGF-A serum levels, as well as VEGFA SNPs, are widely studied in AMD patients. While we did not find any statistical differences in VEGF-A serum levels between the exudative AMD patients and controls, we confirmed results from several other studies which included total AMD patients or only exudative AMD patients, consisting of 27 to 71 samples per group in different populations [53][54][55][56][57][58][59][60]. Further studies revealed significantly elevated VEGF-A levels in exudative AMD patients compared to controls [61,62].…”
Section: Discussionsupporting
confidence: 88%
“…VEGF-A serum levels, as well as VEGFA SNPs, are widely studied in AMD patients. While we did not find any statistical differences in VEGF-A serum levels between the exudative AMD patients and controls, we confirmed results from several other studies which included total AMD patients or only exudative AMD patients, consisting of 27 to 71 samples per group in different populations [53][54][55][56][57][58][59][60]. Further studies revealed significantly elevated VEGF-A levels in exudative AMD patients compared to controls [61,62].…”
Section: Discussionsupporting
confidence: 88%